2023
DOI: 10.3390/polym15102350
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Polyisobutylene Succinic Anhydride (PIBSA) and Its PIBSI Products from the Reaction of PIBSA with Hexamethylene Diamine

Abstract: The nature of the end-groups of a PIBSA sample, namely a polyisobutylene (PIB) sample, where each chain is supposedly terminated at one end with a single succinic anhydride group, was characterized through a combination of pyrene excimer fluorescence (PEF), gel permeation chromatography, and simulations. The PIBSA sample was reacted with different molar ratios of hexamethylene diamine to generate PIBSI molecules with succinimide (SI) groups in the corresponding reaction mixtures. The molecular weight distribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 41 publications
(90 reference statements)
0
1
0
Order By: Relevance
“…Detection of PIB-BSA was based on the preference of intramolecular aggregation of pyrene fragments that resulted in higher fluorescence decay for PIB-BSI-(pyrene)2 in comparison with PIB-BSI-pyrene. In further study of the products of the reaction of PIB-SA with different molar ratios of hexamethylene diamine [136], they found that PIBSA samples comprise 0.50, 0.38, and 0.12 molar fractions of PIB-SA, PIB and PIB-BSA, respectively. Scheme 16.…”
Section: Synthesis Of Pibs With Higher Content Of Trisubstituted Olef...mentioning
confidence: 99%
“…Detection of PIB-BSA was based on the preference of intramolecular aggregation of pyrene fragments that resulted in higher fluorescence decay for PIB-BSI-(pyrene)2 in comparison with PIB-BSI-pyrene. In further study of the products of the reaction of PIB-SA with different molar ratios of hexamethylene diamine [136], they found that PIBSA samples comprise 0.50, 0.38, and 0.12 molar fractions of PIB-SA, PIB and PIB-BSA, respectively. Scheme 16.…”
Section: Synthesis Of Pibs With Higher Content Of Trisubstituted Olef...mentioning
confidence: 99%